NORVASC® IN RUSSIA 20 YEARS LATER: CONTINUATION OF THE HISTORY - A. V. Rudenko; B. A. Rudenko (Рациональная фармакотерапия в кардиологии)
Amlodipine combines the most important clinical effects of calcium antagonists with minimal side effects of both its ATC class  and drugs of previous generations. Its high antihypertensive  activity is not in doubt. Proven ability to improve long-term prognosis is a priority when choosing of amlodipine for treatment of hypertensive patients. This is particularly important for the primary prevention in the presence of both risk factors and associated clinical conditions.  Amlodipine therapy significantly reduced cardiovascular events incidence in patients with atherosclerosis, even if they have no arterial hypertension. The likely rationales for this amlodipine effect are its vasoprotective properties, ability to re- duce vascular stiffness and to slow down the progression of atherosclerosis.